Multiple pathways to evaluate the immunoprotective effect of Turkeys Herpesvirus recombinant vaccine expressing HA of H9N2 - Wenhao Yang; Jin Zhang; Jing Dai; Mengjiao Guo; Xiaolong Lu; Ruyi Gao; Kaituo Liu; Min Gu; Shunlin Hu; Xiufan Liu; Xiaoquan Wang; Xiaowen Liu (Poultry Science)
ABSTRACT: H9N2 avian influenza virus is a significant poultry pathogen that provides internal genes for multiple zoonotic subtypes of avian influenza, presenting a severe threat to public health. The isolation rate of H9N2 in poultry has increased annually in recent years. In this study, a recombinant Herpesvirus of Turkeys (HVT) vaccine expressing H9-HA was constructed using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) technology. In the construction of HVT-EGFP-HA recombinant virus, nonhomologous end joining (NHEJ) is a much more efficient strategy compare to Homology-directed recombination (HDR). HVT-HA demonstrated stability and consistent replication with the parent strain. Subcutaneous injection and in-ovo injection of HVT-HA induced different levels of immune response. Compared to in-ovo injection of HVT-HA, subcutaneous injection induced significantly higher neutralizing serum antibodies. This finding is supported by the significantly higher CD4+ T cell response in Peripheral blood mononuclear cell Peripheral blood mononuclear cell (PBMC) in the subcutaneous injection group. However, in-ovo injection of HVT-HA resulted in significantly higher neutralizing antibodies in the Harderian glands. In addition, it significantly inhibited viral shedding after intranasal exposure to H9N2. This phenomenon could be attributed to the mucosal immunity present in the Hadrian gland. Thus, our findings indicate that the in-ovo injection of the HVT-HA recombinant vaccine is a promising method to inhibit the transmission of H9N2 via the upper respiratory tract in chickens.